2016
DOI: 10.1080/24699322.2016.1236146
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy and the safety of individualized 3D printing screws insertion templates for cervical screw insertion

Abstract: This study verified the safety and the accuracy of the individualized 3D printing screw insertion templates in the cervical spine as a kind of intraoperative screw navigation. This individualized 3D printing screw insertion template was user-friendly, moderate cost, and enabled a radiation-free cervical screw insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 23 publications
0
39
0
2
Order By: Relevance
“…Numerous studies demonstrated that the guides help to lower operation time, with Deng et al (37) suggesting this may decrease complications related to operative time (e.g., infection) (30,35,37,43). Other benefits include decreased intra-operative radiation, simplicity of use, elimination of procedural subjectivity, enhanced pre-operative planning and moderate cost in comparison with other techniques (30,(32)(33)(34)(35)(36)(37)(38)42,43).…”
Section: Surgical Guidesmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies demonstrated that the guides help to lower operation time, with Deng et al (37) suggesting this may decrease complications related to operative time (e.g., infection) (30,35,37,43). Other benefits include decreased intra-operative radiation, simplicity of use, elimination of procedural subjectivity, enhanced pre-operative planning and moderate cost in comparison with other techniques (30,(32)(33)(34)(35)(36)(37)(38)42,43).…”
Section: Surgical Guidesmentioning
confidence: 99%
“…In the cervical spine, asymmetry, vast inter-patient differences such as anomalous vertebral artery course, and the sensitive nature of surrounding tissues make procedural success more difficult to achieve, and hence able to benefit from individualised guides (30,31,33,34,37,38,40,43,56). Otsuki et al (41) demonstrated that 3DP guides provide an extra benefit in revision surgery, where screw insertion is more difficult due to morphology changes caused by the first operation.…”
Section: Surgical Guidesmentioning
confidence: 99%
See 3 more Smart Citations